Wigner crystals for a planar, equimolar binary mixture of classical, charged particles - Antlanger, M.; Kahl, G. (Condensed Matter Physics, 2013)
We have investigated the ground state configurations of an equimolar, binary mixture of classical charged particles (with nominal charges Q₁ and Q₂) that condensate on a neutralizing plane. Using efficient Ewald summation techniques for the calculation of the ground state energies, we have identified the energetically most favorable ordered particle arrangements with the help of a highly reliable optimization tool based on ideas of evolutionary algorithms. Over a large range of charge ratios, q = Q₂ / Q₁, we identify six non-trivial ground states, some of which show a remarkable and unexpected structural complexity. For 0.59 \lesssim q < 1 the system undergoes a phase separation where the two charge species populate in a hexagonal arrangement spatially separated areas. Ми дослiдили конфiгурацiї основного стану еквiмолярної бiнарної сумiшi класичних заряджених части-нок (з номiнальними зарядами Q₁ i Q₂), якi конденсуються на нейтралiзуючiй площинi. Використовуючи ефективний метод пiдсумовування Евальда для обчислення основних енергетичних станiв, ми iденти-фiкували найбiльш енергетично вигiднi впорядкованi розташування частинок за допомогою високо на-дiйного оптимiзацiйного методу, який ґрунтується на iдеях еволюцiйних алгоритмiв. Для великої областi змiни коефiцiєнта зарядiв, q Æ Q₂/Q₁, ми iдентифiкували шiсть нетривiальних основних станiв, деякi з яких демонструють значну i неочiкувану структурну складнiсть. Для 0.59 . q Ç 1, система зазнає фазо-вого розшарування, де зарядженi сорти заселяють просторово вiдокремленi областi з гексагональним розташуванням.